PUSAT KESENIAN DAYAK KALIMANTAN BARAT DI KOTA PONTIANAK - Hendrikus Trivaldo; Uray Fery Andi; Rudiyono Rudiyono (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
West Kalimantan is a province that has a very diverse artistic potential. West Kalimantan Province inhabited by indigenous people and other migrants. The dominant ethnic groups are Dayak, Malay and Chinese. The Dayak tribe is rich in a variety of arts, such as dance, sculpture, painting and others. Every year, the Dayak tribe holds a Dayak Gawai featuring a Dayak art competition. Dayak art was developed by a large number of art studios but not yet well-organized, so a forum for the Dayak Arts Center of West Kalimantan was needed. The purpose of designing the West Kalimantan Dayak Arts Center in Pontianak City is to produce a design for the Dayak arts center of West Kalimantan in Pontianak City as a forum that facilitates Dayak arts in West Kalimantan that reflects the characteristics of Dayak in West Kalimantan. The design method used in the Design of the Dayak Arts Center in West Kalimantan in Pontianak City consists of several stages, namely the idea stage and the data collection stage related to the design needs and the design location. The design result of the West Kalimantan Dayak Arts Center in Pontianak City is to facilitate West Kalimantan Dayak arts based on the functions of education, information, promotion and recreation which can support the activities of West Kalimantan Dayak arts and can display forms that reflect the characteristics of West Kalimantan Dayak architecture.